2018
DOI: 10.1111/jmg.12447
|View full text |Cite
|
Sign up to set email alerts
|

Partial melting due to breakdown of an epidote‐group mineral during exhumation of ultrahigh‐pressure eclogite: An example from the North‐East Greenland Caledonides

Abstract: In the North‐East Greenland Caledonides, P–T conditions and textures are consistent with partial melting of ultrahigh‐pressure (UHP) eclogite during exhumation. The eclogite contains a peak assemblage of garnet, omphacite, kyanite, coesite, rutile, and clinozoisite; in addition, phengite is inferred to have been present at peak conditions. An isochemical phase equilibrium diagram, along with garnet isopleths, constrains peak P–T conditions to be subsolidus at 3.4 GPa and 940°C. Zr‐in‐rutile thermometry on incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 123 publications
(223 reference statements)
0
29
0
Order By: Relevance
“…By working backward, the P-T conditions can be refined by; for example, comparing measured versus predicted mineral compositions and proportions within a calculated field of interest (Powell & Holland, 2008. Examples in the literature applying phase equilibrium modeling to do thermobarometrical calculations are vast (Baziotis et al, 2017;Cao et al, 2019;Dragovic et al, 2020;Groppo et al, 2015;Guevara et al, 2017;Gutiérrez-Aguilar et al, 2021;Hern andez-Uribe et al, 2019;Klonowska et al, 2017;Li et al, 2020;Massonne, 2015;Palin et al, 2012;Štípsk a & Powell, 2005;St-Onge et al, 2013;Wei et al, 2013;Weller et al, 2015; among many others). In the case of forward modeling, petrological calculations can be performed along a sequence of P-T points to determine paragenesis along a given P-T-X path.…”
Section: Introductionmentioning
confidence: 99%
“…By working backward, the P-T conditions can be refined by; for example, comparing measured versus predicted mineral compositions and proportions within a calculated field of interest (Powell & Holland, 2008. Examples in the literature applying phase equilibrium modeling to do thermobarometrical calculations are vast (Baziotis et al, 2017;Cao et al, 2019;Dragovic et al, 2020;Groppo et al, 2015;Guevara et al, 2017;Gutiérrez-Aguilar et al, 2021;Hern andez-Uribe et al, 2019;Klonowska et al, 2017;Li et al, 2020;Massonne, 2015;Palin et al, 2012;Štípsk a & Powell, 2005;St-Onge et al, 2013;Wei et al, 2013;Weller et al, 2015; among many others). In the case of forward modeling, petrological calculations can be performed along a sequence of P-T points to determine paragenesis along a given P-T-X path.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of hydrous silicate melts by dehydration‐driven in situ anatexis has been increasingly recognized in UHP rocks (e.g., review paper of Zheng et al (2011)). Natural and experimental studies suggested that the most likely way of melting the deeply subducted continental crust is dehydration melting of hydrous phases (such as mica‐ and epidote‐group minerals, mainly phengitic muscovite) during a ‘hot’ exhumation (e.g., Auzanneau, Vielzeuf, & Schmidt, 2006; Cao et al, 2019; Hermann, 2002; Hermann et al, 2001; Massonne, 2009; Schmidt, Vielzeuf, & Auzanneau, 2004). Petrographic observations show that there are two types of biotite in the studied migmatite: relict biotite (Figure 2d) and new growth biotite (Figure 2b,c,e–g).…”
Section: Discussionmentioning
confidence: 99%
“…Anatectic process plays a significant role in the evolution of orogenic belts (e.g., Brown, Korhonen, & Siddoway, 2011; Xu & Zhang, 2017), because it strongly influences the thermal and rheological behaviours of orogenic crust (e.g., Whitney, Teyssier, Fayon, Hamilton, & Heizler, 2003). Anatexis of the ultrahigh pressure (UHP) metamorphic rocks has been widely reported in UHP metamorphic terranes, for example, the Sulu UHP terrane of China (e.g., Chen, Zheng, & Hu, 2013a, 2013b; Gao, Xu, Zhang, & Chen, 2018; Song, Xu, Zhang, Wang, & Liu, 2014a, 2014b; Wallis et al, 2005; Xu et al, 2012, 2013,b; Zeng, Liang, Asimow, Chen, & Chen, 2009; Zong et al, 2010), the Kokchetav UHP terrane of Kazakhstan (e.g., Dobretsov & Shatsky, 2004; Hermann, Rubatto, Korsakov, & Shatsky, 2001; Ragozin, Liou, Shatsky, & Sobolev, 2009), the North‐East Greenland Eclogite Province (e.g., Cao, Gilotti, Massonne, Ferrando, & Foster Jr, 2019; Lang & Gilotti, 2007, 2015), and the Western Gneiss Region of Norway (e.g., Labrousse, Jolivet, Agard, Hébert, & Andersen, 2002; Labrousse, Prouteau, & Ganzhorn, 2011). Thus, the nature and timing of the anatexis of the deeply subducted continental crust can help us to understand the tectono‐thermal evolution of the continental collision zones and the exhumation mechanism of UHP metamorphic rocks (e.g., Whitney et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the existing experimental data (Lambert & Wyllie, 1972;Liu, Jin, & Zhang, 2009;Skjerlie & Patino Douce, 2002) and some natural observations (e.g. Cao, Gilotti, & Massonne, 2020;Cao, Gilotti, Massonne, Ferrando, & Foster, 2019;Miyazaki et al, 2016;Nakamura & Hirajima, 2000;Xia, Zheng, & Zhou, 2008) advocate for partial melting of UHP mafic rocks during their exhumation through HP-MP conditions to crustal depths. Most of the studies linked the incipient melting to dehydration melting of phengite (Cao et al, 2020;Gao, Zheng, & Chen, 2012;Liu et al, 2009), whereas some recent research highlight potentially similar role of zoisite, epidote-group minerals or amphibole at least in some cases (Cao et al, 2019(Cao et al, , 2020.…”
Section: Zircon Textures and Inclusionsmentioning
confidence: 99%